Environmental Barriers and Facilitators to Participation of People with Autism Spectrum Disorders: stakeholders’ perspective - Vasilevska Petrovska, Ivana; Giannakopoulou, Angeliki; Giannakopoulou, Anastasia; Winstanley, Angela; Miletto, Roberto; Constanta Rosca, Georgeta; Ivanova, Biserka; Kaisa, Vasiliki; Trajkovski, Vladimir (ReAttach Therapy International Foundation, 2019)
Introduction: Social participation is a vital construct in inclusive philosophies and practices across communities. People with Autism Spectrum Disorders have been facing autism-related and environmental participation restrictions, placing them at risk of social exclusion and institutionalization. A multinational project has been developed in order to identify vital facilitating factors and establish PCP system for persons with ASD and tools for facilitators, as well as a ‘master class’ course for facilitators in several south-eastern European countries. The aim of the study is to identify the most common barriers to participation faced by individuals with ASD and to highlight facilitating factors that can be utilised in development of an autism specific PCP approach. Methodology: a mixed methodology employing concurrent qualitative-quantitative triangulation design was used. The participants consisted of four groups of stakeholders: young people with ASD, parents & family members of children/young people with ASD, teachers, and professionals. The data was collected via interviews and questionnaires with participants from the mentioned groups, using closed-ended and open-ended questions. Results: thematic analysis of the information gathered from the interviews and questionnaires was detailed by topics. Each topic was viewed with regards to barriers and facilitators to social participation. Conclusions: people with ASD have unique support needs that are qualitatively different from other special needs and communities are lacking specific understanding and approaches in meeting those needs. Insights from key stakeholders’ view point represents indispensable considerations in Person-Centred support for overcoming barriers to social participation and promoting health, equity and well-being of persons with ASD.
Keywords: Autism Spectrum Disorders (ASD), social participation, barriers, facilitators, person-centred support, quality of life